A systematic review and meta-analysis of the consequences of female genital mutilation on maternal and perinatal health outcomes in European and African countries. Issue 12 (30th December 2020) - Sylla, Fatoumata; Moreau, Caroline; Andro, Armelle
Abstract : Introduction: Key knowledge gaps remain to improve reproductive health outcomes for millions of women living with female genital mutilation (FGM). We aimed to update previous reviews and quantify more rigorously maternal and perinatal complications related to FGM across different settings. Methods: In this systematic review and meta-analysis, we searched 15 electronic databases for studies published between 1 August 1995 and 15 March 2020, reporting on maternal and perinatal complications related to FGM. We included studies comparing women with and without FGM while accounting for confounders. Pooled relative risks (RR) were calculated, using fixed-effects and random-effects models, for a range of maternal and perinatal outcomes, adjusting for individual characteristics and according to delivery settings and study design. Results: We identified 106 unique references, assessed 72 full-text articles and included 11 studies. We found non-significant elevated risks of instrumental delivery, caesarean delivery, episiotomy, postpartum haemorrhage, perineal laceration, low Apgar score and miscarriage/stillbirth related to FGM. Heterogeneity was present for most outcomes when combining all studies but reduced in subgroup analyses. The risk of caesarean delivery was increased among primiparous women (1.79, 95% CI 1.04 to 3.07) such as the risk of episiotomy in European specialised settings for women with FGM (1.88, 1.14 to 3.09). In Africa, subgroup analyses revealed elevated risks of postpartum haemorrhage (2.59, 1.28 to 5.25). The most common reported type was FGM II. However, few studies provided stratified analyses by type of FGM, which did not allow an assessment of the impact of the severity of typology on studied outcomes. Conclusion: This review suggests maternal and perinatal morbidity related to FGM vary by study design, context and by subgroup of women. Our study also draws attention to the complications that may extend to the postpartum period. This work contributes to shaping a reference framework for future research and clinical guidelines.